PF.32 Partial Urorectal Septum Malformation (pURSM) Sequence in England and Wales: Prevalence, Additional Anomalies, and Pregnancy Outcome. (26th April 2013) - Tennant, PWG; Glinianaia, SV; Wellesley, D; Rankin, J
Abstract : Background: Partial urorectal septum malformation (pURSM) sequence (or 'persistent cloaca') is a rare congenital anomaly characterised by a confluence of the urethral, anal, and genital openings. This study describes the prevalence, additional anomalies, and pregnancy outcomes of pURSM sequence in England and Wales. Methods: All cases of pURSM sequence notified to seven congenital anomaly registers in England and Wales during 1985–2010, whether delivered as live births, spontaneous fetal deaths (≥20 weeks gestation), or elective terminations of pregnancy for fetal anomaly (any gestation), formed this population-based case series. Risks of spontaneous fetal and infant death were examined by the Kaplan-Meier method. Differences in prevalence over time, and between regions, were examined by multilevel Poisson regression. Results: 117 cases were recorded among 4, 251, 241 total births. 58 (50%) were delivered as live births, 6 (5%) as spontaneous fetal deaths, and 53 (45%) as elective terminations. The total prevalence was 2.8 (95% CI: 2.3–3.4) per 100, 000 total births, increasing significantly over time (p = 0.002) and differing significantly between regions (p = 0.005). 77 cases (66%) had at least one additional major congenital anomaly outside the perineum, including 67 (57%) with renal, 29 (25%) with musculoskeletal, 26 (23%) with digestive system, and 24 (21%) with cardiovascular anomalies. The risks of spontaneous fetal and infant death were estimated as 8.9% (95% CI: 4.1–18.8) and 26.3% (95% CI: 15.1–43.4) respectively. Conclusions: This is the largest study of the epidemiology of pURSM sequence. This information should be valuable for families and health professionals whenever a case of pURSM sequence is diagnosed.